Agreement On Agriculture Dalam World Trade Organization - Patra, Akbar Kurnia (Jurnal Hukum & Pembangunan, 2016)
Framework of agricultural trade liberalization in the context of World Trade Organization (WTO) General Agreement set out in the field of Agriculture or the Agreement on Agriculture (AOA). AOA is one of the international treaties that are generated through a series of WTO negotiations in the Uruguay Round of General Agreement on Tariffs and Trade (GATT). Pact is applied simultaneously with the establishment of the WTO on January 1, 1995 which contained 13 parts and 21Articles which is equipped with 5 Annex and an appendix to the Annex 5. The AoA has three main pillars, namely the expansion of market access, domestic support and export subsidies. Through Law No. 7 of 1994, Indonesia has ratffied the WTO provisions which obliges WTO member states to adapt the rules contained in Annex WTO. One of them is the rules of the food policy Indonesia through Law No. 7 of 1996 concerning Food and Government Regulation No. 68 of 2002 on Food Security